Skinny brown dog - Holt, Kimberly Willis (Henry Holt, 2007)
Benny the baker sees no need for a dog in his life, but while his most faithful customer and the children who visit his bakery for "Free cookie day" soon realize he has been adopted by a stray, it takes a heroic deed to convince Benny that the dog belongs with him.